In silico analysis of cross reactivity among phospholipases from Hymenoptera species (2021)
ABSTRACT: Background: Phospholipases are enzymes with the capacity to hydrolyze membrane lipids and have been characterized in several allergenic sources, such as hymenoptera species. However, cross-reactivity among phospholipases allergens are little understood. The objective of this study was to determine potential antigenic regions involved in cross-reactivity among allergens of phospholipases using an in silico approach. Methods: In total, 18 amino acids sequences belonging to phospholipase family derived from species of the order hymenoptera were retrieved from the UniProt database to perform phylogenetic analysis to determine the closest molecular relationship. Multialignment was done to identify conserved regions and matched with antigenic regions predicted by ElliPro server. 3D models were obtained from modeling by homology and were used to locate cross-reactive antigenic regions. Results: Phylogenetic analysis showed that the 18 phospholipases split into four monophyletic clades (named here as A, B, C and D). Phospholipases from A clade shared an amino acid sequences' identity of 79%. Antigenic patches predicted by Ellipro were located in highly conserved regions, suggesting that they could be involved in cross-reactivity in this group (Ves v 1, Ves a 1 and Ves m 1). Conclusions: At this point, we advanced to the characterization of potential antigenic sites involved in cross-reactivity among phospholipases. Inhibition assays are needed to confirm our finding.